La Nouvelle Peinture Allemande dans la Collection Ludwig, Aix-la-Chapelle. - Baselitz, Georg; Becker, Wolfgang; Brock, Bazon; Büttner, Werner; Celan, Paul; Crone, Rainer; Davvetas, Démosthènes; Grobe, Rolf; Harten, Jürgen; Hoenjet, Frank; Kornbichler, Thomas; Lüpertz, Markus; et al. (Lyon : Goethe Institut Centre Culturel Allemand, 1987)
Baselitz, Georg ; Bömmels, Peter ; Büttner, Werner ; Dahn, Walter ; Dokoupil, Jiri Georg ; Fetting, Rainer ; Immendorff, Jörg ; Kiefer, Anselm ; Kippenberger, Martin ; Lüpertz, Markus ; Middendorf, Helmut ; Oehlen, Albert ; Oehlen, Markus ; Penck, A.R. ; Richter, Gerhard
La Nouvelle Peinture Allemande dans la Collection Ludwig, Aix-la-Chapelle 1986/87, Musée St. Pierre Art Contemporain, Lyon, Musée Cantini, Marseille, Musée des Augustins, Toulouse, Musée d'Art Moderne de Villeneuve d'Ascq, Lille, Musée des Beaux-Arts, Nantes
Frans
boek
Keywords: Duitsland